IMPACT OF DOCKING KARADI LAMBS ON SOME BLOOD BIOCHEMICAL PARAMETERS - Dler Al-Sherwany; Jalal Alkass (Mesopotamia Journal of Agriculture)
To study the effect of docking on some blood parameters, 12 Karadi lambs were docked at birth and reared by their dams till weaning, and 12 weaned intact Karadi lambs were bought from the market. Following weaning, the docked (16.83±1.522kg) and intact (19.92± 0.748kg) lambs were distributed equally into 3 treatment groups to be slaughtered at 20, 30 and 40kg. The findings demonstrated that the overall mean of serum total protein, urea, creatinine, glucose, triglyceride, cholesterol, LDL and HDL were 5.50±0.13 g/dl, 30.56±1.39, 0.79±0.05, 63.61±3.48, 30.51±3.81, 51.87±4.12, 20.29±2.83 and 34.73±3.53mg/dl, respectively. It seems that docked lambs had numerically higher serum total protein, glucose and triglyceride, and lower serum urea, creatinine, cholesterol, LDL and HDL than intact lambs. Also it was shown that an increase in live body weight resulted in a decrease in LDL, VLDL, triglyceride and cholesterol, and an increase in total protein and HDL. It can be concluded that docking has no effect on studied traits.